Public Relation Moderates Between Sales Promotion With Purchase Decisions On XX Ready Foods In 2020 - Asyidatur Rosmaniar; Marista Oktaviani; Nurullaili Mauliddah (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2021)
This study is entitled moderating public relations between sales promotion and purchasing decisions on XX ready food in 2020; this research is a descriptive study using a quantitative approach. A sample of 90 respondents who are consumers of fast food, data collection methods using questionnaires. The data analysis technique used is the SEM model analysis of the SmartPls analysis tool. The results showed that sales promotion has a significant positive effect on purchasing decisions, and public relations quasi moderates between sales promotion and purchasing decisions. ABSTRAK Penelitian ini berjudul public relations memoderasi antara promosi penjualan dan keputusan pembelian makanan siap saji XX tahun 2020; Penelitian ini merupakan penelitian deskriptif dengan pendekatan kuantitatif. Sampel sebanyak 90 responden yang merupakan konsumen fast food, metode pengumpulan datanya menggunakan kuesioner. Teknik analisis data yang digunakan adalah analisis model SEM dengan alat analisis SmartPls. Hasil penelitian menunjukkan bahwa promosi penjualan berpengaruh positif signifikan terhadap keputusan pembelian dan hubungan masyarakat quasi moderat antara promosi penjualan dan keputusan pembelian.